2007
DOI: 10.1007/s11060-007-9462-8
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular application of TNF-alpha impairs cell to cell communication via gap junctions in glioma cells

Abstract: Human gliomas are the most common class of brain neoplasm. In order to better characterize their response to inflammation, we evaluated the influence of tumor necrosis factor alpha (TNF-alpha) on the coupling behaviour and the membrane resting potential (MRP) of glioma cells (F98 glioma cell line) compared to primary astrocytes. In contrast to cultured primary astrocytes which exhibited a profound inhibition of gap junction mediated intercellular communication (GJIC), extracellular exposure of TNF-alpha to F98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…These data are in accordance with previous studies that reported IL-1β downregulates the expression of Cx43 in astrocyte-rich cultures2122. However, our present data differ from previous reports regarding the effects of proinflammatory cytokines on glial cells2324. Haghikia et al .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These data are in accordance with previous studies that reported IL-1β downregulates the expression of Cx43 in astrocyte-rich cultures2122. However, our present data differ from previous reports regarding the effects of proinflammatory cytokines on glial cells2324. Haghikia et al .…”
Section: Discussionsupporting
confidence: 88%
“…Haghikia et al . reported that TNFα inhibits the function of GJs in astrocyte/microglia co-cultures containing 5% microglia derived from rat brain23. Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…On analysis of a subset of our samples (20) from GBM patients and normal controls (14), we did not find a significant difference in the mean levels of circulating TNFα as measured by ELISA (data not shown). TNF-R1 is expressed by glioma tumor cell lines [43, 44] whereas TNF-R2 is expressed by some, but not all glioma cell lines [43] and shedding of both TNF-R1 and TNF-R2 by glioma cell lines has been described [45]. Microrarray analysis indicates overexpression of TNF-R1 in some GBM tumors where RNA was extracted from whole tumors [29, 46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in astrocyte cultures not devoid of microglia, LPS or pro-inflammatory cytokines reduce astroglial coupling via nitric oxide synthase (NOS) induction and a p38 kinase-dependent pathway (40, 91, 139, 164, 235, 408). Both the IL-1 β and TNF- α effects on gap junctions occur as early as 2 h after application (139, 408). Because this latency is close to the half-life of Cx43 (197), the action may be due to block of synthesis or increase in degradation of Cx.…”
Section: Glial Cells and Their Implication In Neurodegenerative Diseasesmentioning
confidence: 99%